Frequency of dermatophytes fungus in the breeding guinea pig (cavia porcellus) in the province of Huánuco - Pineda Castillo, Carlos A. (2009)
The dermatosis is a permanent problem in guinea pigs. Many producers, even veterinarians, manage the problem as an acariasis solely. The lack of diagnosis test and no-specific treatment to extend the problem. We analyzed 26 guinea pig's samples, of both sexes, all the ages and zootechnical types; the samples came from small farms of the Province of Huanuco between June and November. It was identified Trichophyton mentagrophytes in 50% of the samples, concomitant to acarosis. This problem appeared mainly in the fatten stage and any type of operation, pit or cages. It is recommended the diagnosis test previous to any treatment; which will have to consider the use of some anti-fungal; besides to set up control's measures and prophylaxis inside and outside of the facilities, and the use of alternative medicine, testing anti-fungal activity that offer some plants of our region.